Evaluasi Terhadap Program Planet Sains pada Siaran TV Edukasi untuk Sekolah Menengah Pertama - Suhartini Suhartini (Lembaga Penelitian dan Pengabdian kepada Masyarakat, Universitas Negeri Jakarta, 2014)
The research aims are to evaluate four aspects of broadcast management instructional programs, those are: planning, production, execution, and monitoring and evaluation used a qualitative approach. The evaluation used Provus evaluation model, conducted at Pustekkom and three Junior High Schools. The data from questionnaires, observation, interview, and documentation, analyzed using Miles and Huberman models. The results described that: 1) program planning was less focused; 2) production process has been done procedurally, but host rated rigid; 3) execution schedules are not on target and less promotion; and 4) monitoring and evaluation program conducted only when preview, whereas when on air and after is not performed special call on the program. Inferred that, this program deserves to broadcast and used as an enrichment program in science instruction.